Is the oral fungal pathogen Candida albicans a cariogen? - Pereira, D. F.A. [UNESP]; Seneviratne, C. J.; Koga-Ito, C. Y. [UNESP]; Samaranayake, L. P. (Wiley, 2018)
Pathobiology of dental caries is complex. Data from recent molecular microbiologic studies have further redefined the role of the oral microbiome in the etiology of dental caries. This new information challenges the conventional view on the hegemony of classic cariogenic prokaryotes such as Streptococcus mutans in caries etiology, and raises the intriguing possibility of the participation of the eukaryotic oral fungal pathogen Candida in the caries process. The virulence attributes of Candida species such as their acidogenicity and aciduric nature, the ability to develop profuse biofilms, ferment and assimilate dietary sugars, and produce collagenolytic proteinases are all indicative of their latent cariogenic potential. Based on the above, oral candidal counts have been used by some as a caries risk indicator. On the contrary, other studies suggest that Candida is merely a passenger extant in an acidic cariogenic milieu, and not a true pathogen. In this review, we critically examine the varying roles of Candida, and traditionally accepted cariogens such as the mutans group of streptococci in the pathobiology of dental caries. The weight of available data tends to imply that Candida may play a pivotal role as a secondary agent perpetuating the carious process, especially in dentinal caries.
Keywords: Candida albicans; caries; cariogenicity